Empowering farmers in Embu County: Adoption of gender transformative Socio-Technical Innovation Bundles (STIBs) and their impact on resilience, productivity, and food security - Lutomia, Cosmas Kweyu; Ketema, Dessalegn; Muriithi, Catherine; Nchanji, Eileen Bogweh (2025)
This infographic presents evidence from Embu County on the adoption and outcomes of gender-transformative socio-technical in novation bundles (STIBs). It highlights uptake patterns across wards, gender, and innova tion types — technical, technological, and so cial. The visualizations illustrate how STIBs in fluence resilience, productivity, food security, and empowerment among smallholder farm ers in the county. Findings are intended to in form inclusive scaling strategies across policy, program, and investment domains.